Potential of bioaugmentation of heavy metal contaminated soils in the Zambian Copperbelt using autochthonous filamentous fungi - Dusengemungu, Leonce; Gwanama, Cousins; Simuchimba, Grant; Mubemba, Benjamin (Frontiers in Microbiology, 2022)
Filamentous fungi present in heavy metals (HMs) contaminated environments have a great potential for bioaugmentation, although they're still poorly investigated in developing countries such as Zambia. Therefore, this research aimed at exploring the bioaugmentation potential of filamentous fungi consortium in heavy metal contaminated soil. The conventional streak plate method was used to isolate fungi from heavy metal contaminated soil. Filamentous fungi isolates were identified utilizing morphological and molecular techniques. The radial growth diameter technique evaluated the heavy metal tolerance of fungi. Three indigenous fungi were used for the bioaugmentation experiment. The most abundant, highly tolerant fungi consortium (Aspergillus oryzae, Cladosporium pseudocladosporioides, and Geotrichum candidum species) were used to bioremediate the copper and cobalt contaminated soil; simultaneously, the uncontaminated soil was employed as a control. The maximum tolerance index of 1.0 was observed with Aspergillus oryzae, Cladosporium pseudocladosporioides, and Geotrichum candidum species in the presence of a high concentration of Cu, Co, Fe, Mn, Pb, and Zn. The maximum Cu, Co, Fe, Mn, Pb, and Zn bioremoval capacity of a highly tolerant blended fungal consortium of treated soil was examined after 90 days and was recorded as Cu:75.09%, Co:99.8%, Fe:62.9%, Mn:84.7%, Pb:100%, and Zn:100%. There was a high distinction between the treated and untreated contaminated soil. The present study has harnessed the potential of high resistant fungal isolates to remediate the heavy metal contamination conundrum.